Liver Dysfunction in Perinatal Asphyxia - Jaswir Singh; Anil Kumar Poonia (JCDR Research and Publications Pvt. Ltd., 2019)
Introduction: Liver dysfunction in perinatal asphyxia may be manifested by elevation of hepatocellular enzymes. It affects the outcome of perinatal asphyxia in newborn. Aim: To study the effect of perinatal asphyxia on liver function. Materials and Methods: This study was conducted on 100 newborns with perinatal asphyxia and 50 healthy newborns were taken as control group. Baby with APGAR score <7 at 1 minutes, fetal heart variation and meconium passage in utero were considered to have perinatal asphyxia. Qualitative data was analysed statistically by Person ChiSquare test. Numerical analysis was done by mean, SD and independent t-test. Results: The study included 59 male babies and 41 female babies in the case group and 25 male babies and 25 female babies in control group. Mean gestational age in case group was 37.29±2.1 weeks and in control group was 37.06±2.25 weeks. The difference between perinatal asphyxia and control group was highly significant for Serum Glutamate Oxaloacetic Transaminase (SGOT), Serum Glutamate Pyruvic Transaminase (SGPT) and Alkaline Phosphatase (ALP) (p<0.001) and significant for Total Serum Bilirubiun (TSB) (p<0.025). The difference between fetal asphyxia alone and control group was highly significant (p<0.001) for SGOT, SGPT and significant for ALP (p=0.002) and TSB (p=0.009) respectively. In birth asphyxia alone group, the difference was highly significant for SGOT, SGPT, ALP (p<0.001) and significant for TSB (p=0.034) as compared to control group. Conclusion: Early detection of hepatic dysfunction helps to predict the complication of hepatic dysfunction and their early treatment.